INVESTIGATING STOCK MARKET REACTION ON JAKARTA ISLAMIC INDEX (JII) ANNOUNCEMENT - Laila, Nisful; Nasih, Mohammad (Journal of Innovation in Business and Economics, 2013)
The aim of this research is to investigate the stock market reaction from the event when Jakarta Islamic Index (JII) is announced. The indication of stock market reaction was shown by appearing abnormal return during the date when the emiten are in the list of JII, and also several days before and after the annaouncement day. The method of this research is called event studies. Data collected from daily stock price from Indonesian Stock Exchange data base. By using market adjusted model, it was found that 21 stocks from JII latest list, during 11 days observation shown significant abnormal return, at 5% significant level. The conclusion from this finding is that the information of JII announcement has important content that caused the abnormal return during and around the announcement day. Moreover the information is shown a positive signal for investor, so that caused positive abnormal return